Oficina de cordas como formação musical na educação do Campo: um estudo de caso - Reis, Valdivino Neres dos (Universidade Federal do Tocantins, 2020)
This paper aims to present a study on the musical pedagogical processes developed in the string workshop extension project, whose theoretical basis is the David Elliott praxial concept applied to the collective teaching of musical instruments, such as: cello, viola of arco, violin y, which aims at learning, experience, interpretation and contextualization of music as an agglutinating element of musical learning. Methodologically, the research follows a qualitative approach, with the intention of understanding the phenomena in the most detailed way possible. From the point of view of the technical procedures, the investigation led to the realization of a case study, specifically on the extension project of the extension workshop developed on the university campus of professor Sérgio Jacintho Leonor /Araias / UFT. The case study option is due to the fact that it gathers densely descriptive data through field diaries, interviews and observations of the participants. The study revealed that the teaching and learning activities developed in the project contributed positively to complement the knowledge and musical training of future field education degree music educators with a degree in visual arts and music. The project has brought advantages mainly because it provides the application of a different way of teaching and provides the opportunity for many people to study music. The workshop helped in the